PEMBUATAN BAHAN AJAR FISIKA BERBASIS WEB PADA KONSEP TERMODINAMIKA UNTUK PEMBELAJARAN MENURUT STANDAR PROSES SISWA KELAS XI SMA - Nozi Opra Agustian (Universitas Negeri Padang, 2013)
Learning material can support the learning process in the classroom. It can be used to reach the purpose of learning. One solution to support the learning process through physics learning materials based on website. The purpose of this research is to produce good description, validity, practicality, and effectivity of physics learning material based on Website in concept of Thermodynamics. Object of this research is physics learning material based on website in concept of Thermodynamics and second grade students of Senior High School. The instruments are used to collect the data in this research are: validity sheet, practicality sheet, and learning outcome test sheet. There are four result of this research based on analyze of the data. First, Physics learning materials based on website has high validity score 83.54. Second, design Physics learning material based on website consist of introduction, competence, objectives, contents, competence test, evaluation, reference, chat and forum. Third, the value of practicality of Physics learning material based on website according to teacher and students each other 89,51 and 75,89. Finally, Physics learning material based on website in concept of Thermodynamics effectives to increase learning outcomes of students. Keywords – Physics, Learning Material, Website, Thermodynamics, Validity, Practicality, Effectivity